2005
DOI: 10.1002/ejoc.200500364
|View full text |Cite
|
Sign up to set email alerts
|

Isolation of Plakinamine I: A New Steroidal Alkaloid from the Marine Sponge Corticium sp. and Synthesis of an Analogue Model Compound

Abstract: A new cytotoxic steroidal alkaloid, plakinamine I, with an unprecedented 3α-amino-19-acetoxy nucleus was isolated from a Corticium sp. sponge. The structure has been elucidated by spectroscopic analysis and secured by the synthesis of the model 19-acetoxy-3α-aminocholestane. The evaluation of the cytotoxic activities of several synthetic derivatives, in-

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0

Year Published

2006
2006
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 12 publications
0
13
0
Order By: Relevance
“…The presence of two dimethylamino groups in 1 was suggested by the resonances observed as two broadened singlets (δ H 2.84 and δ H 2.85) integrating for 12 protons attached to carbon resonances observed at δ C 42.7 and 40.5. A literature search suggested that similar resonances are found in the plakinamine class of natural products [5][6][7][8][9][10][11][12][13][14][15] and comparison of the NMR data to the published data suggested that 1 is most similar to plakinamines L and M [14,15]. Other characteristic resonances observed in the 1 H NMR spectrum of 1 were the methyl resonances observed at δ H 0.59 (H 3 -18, s) and δ H 0.86 (H 3 -19, s), which are consistent with the angular methyl groups of a steroidal alkaloid.…”
Section: Chemical Analysismentioning
confidence: 88%
See 2 more Smart Citations
“…The presence of two dimethylamino groups in 1 was suggested by the resonances observed as two broadened singlets (δ H 2.84 and δ H 2.85) integrating for 12 protons attached to carbon resonances observed at δ C 42.7 and 40.5. A literature search suggested that similar resonances are found in the plakinamine class of natural products [5][6][7][8][9][10][11][12][13][14][15] and comparison of the NMR data to the published data suggested that 1 is most similar to plakinamines L and M [14,15]. Other characteristic resonances observed in the 1 H NMR spectrum of 1 were the methyl resonances observed at δ H 0.59 (H 3 -18, s) and δ H 0.86 (H 3 -19, s), which are consistent with the angular methyl groups of a steroidal alkaloid.…”
Section: Chemical Analysismentioning
confidence: 88%
“…Detailed results from NMR analysis are shown in Table 1. The relative configuration of 1 was defined based upon the ROESY and NOESY data ( Figure 2 and Supplementary S13, S21-S23, Table S2) as well as comparison with previously described plakinamines [5][6][7][8][9][10][11][12][13][14][15]. NMR data were collected in two different solvents to fully resolve the A ring protons with DMSO-d 6 yielding sufficient resolution.…”
Section: Chemical Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…34) Oxidation at C-19 and subsequent rearrangement might occur to give the abeo-9(10-19)-type skeleton, supported by the isolation of 19-acetoxylated alkaloid plakinamine I. 35) Furthermore, stigmastane-type steroidal alkaloids having an N-methyl piperidine unit, together with an N-methyl pyrrolidine unit in the side chain, have also been isolated. 36,37) Proliferation and migration of HUVECs requires the activation of ERK1/2 mitogen-activated protein kinase (MAPK) and p38 MAPK pathways induced by a growth factor, such as VEGF and bFGF.…”
Section: Cortistatins From the Marine Spongementioning
confidence: 95%
“… 27 29 The cortistatins have demonstrated antiangiogenic properties, 30 while the plakinamines have been reported to exhibit diverse biological effects including anti-HIV, 19 antimicrobial, 20 and cytotoxic activities. 17 , 19 , 21 23 , 26 The C. niger extract identified in the current study was subjected to a bioassay-guided fractionation procedure that monitored cytotoxic activity against COLO205 and KM12 colon cancer cell lines. Sequential chromatographic separations employing diol SPE, Sephadex LH-20, and C 18 HPLC led to the isolation of two new metabolites, plakinamine N ( 1 ) and plakinamine O ( 2 ), along with two previously described plakinamines, 3 and 4 .…”
mentioning
confidence: 99%